Polymorphism of the complement 5 gene is associated with large artery atherosclerosis stroke in Chinese patients - Wu, Hui; Weng, Yingfeng; Zheng, Lan; Li, Huanyin; Gong, Qi; Fu, Yi; Zhao, Jing (Arquivos de Neuro-Psiquiatria, 2016)
The complement system has been confirmed to play an increasingly important role in ischemic stroke (IS). This study aimed to determine whether the single-nucleotide polymorphism of the complement 5 (C5) gene independently influences the occurrence, severity, and long-term outcome of IS in Chinese patients. Methods C5 rs17611 genetic variants were investigated in 494 IS patients and 330 control individuals .Ischemic stroke was classified into subtypes and patients were assessed 90 days post-stroke with the modified Rankin Scale to determine stroke outcome.Results The presence of C5 polymorphism was associated with the incidence of large artery atherosclerosis (LAA)-subtype IS (n =2 00; p = 0.031), which even persisted after adjustment for covariates (OR = 1.518; 95%CI = 1.093–2.018; p = 0.013). However, no association was found between genotypes and the severity and outcome of stroke (p = 0.978; p = 0.296).Conclusions The C5 polymorphism might contribute to the risk of LAA-subtype IS independently of other known risk predictors.
Keywords: genes; stroke